A clinical case of anaphylactic shock development after anesthesia induction - K. N. Khrapov; A. A. Khryapa; I. V. Vartanova; S. S. Sedov; Yu. S. Okhapina; E. G. Gavrilova (Вестник анестезиологии и реаниматологии)
The article describes a clinical case when a patient who was supposed to have a planned surgery on the spine developed anaphylactic shock. After 10 minutes of anesthesia introduction, the patient developed severe hypotension (resistant to the administration of adrenomimetics) and tachycardia; a decrease in the partial pressure of carbon dioxide at the end of expiration was noted. Due to the rapid development of a critical condition, the absence of specific skin manifestations and allergic history, as well as a direct association with the administration of a specific agent, it was necessary to carry out a differential diagnosis between acute myocardial infarction, pulmonary embolism, and anaphylactic shock. During the intensive care, the patient had echocardiography and ECG, blood gases were tested; the decisive diagnostic factor was the identification of bronchospasm signs. When the condition was stabilized, angiography of the vessels of the heart and lungs was performed; later, the agent that caused the development of anaphylaxis was established.Identifying the cause of hypotension after induction of anesthesia is critical because therapy can vary significantly. The development of anaphylactic shock during general anesthesia is not common but delayed diagnosis and therapy can be fatal. The article discusses modern approaches to the diagnosis and therapy of perioperative anaphylaxis using the example of the presented clinical case.